Evaluation of internal adaptation of Class V resin composite restorations using three techniques of polymerization (Journal of Applied Oral Science, 2007)
OBJECTIVE: The purpose of this in vitro study was to evaluate the internal adaptation of Class V composite restorations to the cavity walls using three different techniques of polymerization. METHODS: Standard cavities were prepared on the buccal and lingual surfaces of 24 extracted human third molars with margins located above and below the cementoenamel junction. Restorations were placed in one increment using two restorative systems: 3M Filtek A110/ Single Bond (M) and 3M Filtek Z250/ Single Bond (H) in the same tooth, randomly in the buccal and lingual surfaces. Resin composites were polymerized using three techniques: Group 1 - Conventional (60 s - 600 mW/cm²); Group 2 - Soft-start (20 s - 200 mW/cm² , 40 s - 600 mW/cm²); Group 3 - Pulse Activation (3 s - 200 mW/cm², 3-min hiatus, 57 s - 600 mW/cm²). Buccolingual sections were polished, impressions taken and replicated. Specimens were assessed under scanning electron microscopy up to X1000 magnification. Scores were given for presence or absence of gaps (0 - no gap; 1 - gap in one wall; 2 - gap in two walls; 3 - gap in three walls). RESULTS: The mean scores of the groups were (±SD) were: G1M-3.0 (± 0.0); G2M-2.43 (± 0.8); G3M- 1.71 (± 0.9); G1H- 2.14 (± 1.2); G2H- 2.00 (± 0.8); G3H- 1.67 (± 1.1). Data were analyzed using Kruskal-Wallis and Dunnet's tests. No statistically significant difference (p>;0.05) was found among groups. Gaps were observed in all groups. CONCLUSIONS: The photocuring technique and the type of resin composite had no influence on the internal adaptation of the material to the cavity walls. A positive effect was observed when the slow polymerization techniques were used.